The Myth of the Mundane: The Symbolism of Mud Brick and Its Architectural Implications - Silva, Luiza Osorio G..
The Egyptological truism that mud brick was simply mundane limits our understanding of the material and how it functioned in architecture. In order to explore the possible meanings of the brick medium beyond its tie to the mundane and its practical functions, this study focuses on the symbolism of brick objects. This can be seen in the presence of model bricks and brick molds in foundation deposits, in the molding of bricks by the king in foundation rituals, in the personification of bricks as a goddess of birth and the use of ritual birth bricks, and in the placement of magical bricks in tomb walls. Together with textual references that speak of the connection of mud to the inundation and the creation of the world, this symbolism suggests an association of the mud-brick architectural medium with creation and life cycles, and thus neheh time, as well as archaic architecture. This reinterpretation will be used to re-evaluate the employment of bricks in the specific contexts of the Middle Kingdom pyramids, temple annexes, and royal palaces. The architectural use of bricks will also be contextualized in matters of materials choice more generally, highlighting the need for both brick and stone in cosmologically significant architecture. doi: http://dx.doi.org/10.5913/jarce.56.2020.a012